A short primer for sequencing DNA cloned in the single-stranded phage vector M13mp2. - Anderson, S (1980)
In this paper we describe the synthesis and cloning of a short segment of DNA complementary to the region immediately adjacent to the EcoRI insertion site in the single-stranded bacteriophage vector M13mp2. This segment is useful as a "universal" primer for DNA sequencing by the dideoxynucleotide chain termination method; the template can be any DNA species cloned in M13mp2 or its derivatives. The primer has been cloned into the tetracycline resistance gene of plasmid pBR322 as one strand of a 26 bp EcoRI/BamHI fragment. This fragment may be readily prepared from an EcoRI + BamHI restriction digest of the parent plasmid (designated pSP14) by a simple size fractionation.